Molecular epidemiology of Clostridioides difficile in companion animals: Genetic overlap with human strains and public health concerns - Alves, Frederico; Castro, Rita; Pinto, Miguel; Nunes, Alexandra; Pomba, Constança; Oliveira, Manuela; Silveira, Leonor; Gomes, João Paulo; Oleastro, Mónica (Frontiers in Public Health, 2023)
The changing epidemiology of Clostridioides difficile reflects a well-established and intricate community transmission network. With rising numbers of reported community-acquired infections, recent studies tried to identify the role played by non-human reservoirs in the pathogen’s transmission chain. This study aimed at describing the C. difficile strains circulating in canine and feline populations, and to evaluate their genetic overlap with human strains to assess the possibility of interspecies transmission. Faecal samples from dogs (n=335) and cats (n=140) were collected from two populations (group A and group B) in Portugal. C. difficile isolates were characterized for toxigenic profile and PCR-ribotyping. The presence of genetic determinants of antimicrobial resistance was assessed in all phenotypically resistant isolates. To evaluate the genetic overlap between companion animals and human isolates from Portugal, RT106 (n=42) and RT014/020 (n=41) strains from both sources were subjected to whole genome sequencing and integrated with previously sequenced RT106 (n=43) and RT014/020 (n=142) genomes from different countries. The genetic overlap was assessed based on core-single nucleotide polymorphism (SNP) using a threshold of 2 SNP. The overall positivity rate for C. difficile was 26% (76/292) in group A and 18.6% (34/183) in group B. Toxigenic strains accounted for 50% (38/76) and 52.9% (18/34) of animal carriage rates, respectively. The most prevalent ribotypes (RT) were the toxigenic RT106 and RT014/020, and the non-toxigenic RT010 and RT009. Antimicrobial resistance was found for clindamycin (27.9%), metronidazole (17.1%) and moxifloxacin (12.4%), associated with the presence of the ermB gene, the pCD-METRO plasmid and point mutations in the gyrA gene, respectively. Both RT106 and RT014/020 genetic analysis revealed several clusters integrating isolates from animal and human sources, supporting the possibility of clonal interspecies transmission or a shared environmental contamination source. This study shows that companion animals may constitute a source of infection of toxigenic and antimicrobial resistant human-associated C. difficile isolates. Additionally, it contributes with important data on the genetic proximity between C. difficile isolates from both sources, adding new information to guide future work on the role of animal reservoirs in the establishment of community associated transmission networks and alerting for potential public health risk.